65.6k views
1 vote
Please HELP ASAP I really need help

Please HELP ASAP I really need help-example-1

2 Answers

3 votes

ANSWER


f(g(x)) = 16 {x}^(4) -3 2{x}^(2) +18

EXPLANATION

The given functions are:


f(x)={x}^(2) - 2x + 3

and


g(x) = 4 {x}^(2) - 3

We want to find


f(g(x)) = f(4 {x}^(2) - 3)

This implies that;


f(g(x)) = ( 4 {x}^(2) - 3)^(2) - 2(4 {x}^(2) - 3) + 3

We expand to get,


f(g(x)) = 16 {x}^(4) - 24 {x}^(2) + 9- 8 {x}^(2) + 6+ 3


f(g(x)) = 16 {x}^(4) -3 2{x}^(2) +18

User Renatopp
by
4.1k points
1 vote

Answer:


f(g(x)) = 16x ^ 4-32x ^ 2 + 18

Explanation:

we have two functions


f (x) = x ^ 2 -2x + 3\\\\g (x) = 4x ^ 2-3

We wish to find the compound function f(g(x))

To find f(g(x)) you must introduce the function g(x) within the function f(x). This is change the variable x, in the function f(x), by g(x).


f (g (x)) = (4x ^ 2-3) ^ 2 - 2 (4x ^ 2-3) +3

Now simplify the expression:


f (g (x)) = 16x ^ 4-24x ^ 2 + 9 - 8x ^ 2+6 +3\\\\f(g(x)) = 16x ^ 4-32x ^ 2 + 18

User Vitalizzare
by
4.8k points